Gender variance in children and adolescents with autism spectrum disorder from the National Database for Autism Research. Issue 1 (2nd January 2017) - May, Tamara; Pang, Kenneth; Williams, Katrina Jane
ABSTRACT: Previous studies suggest elevated rates of gender variance (GV), the wish to be of the other gender, in those with autism spectrum disorder (ASD). This study aimed to understand the rate of GV in children and adolescents with ASD and explore differences in sex, age, and emotional-behavioral problems relative to those referred to clinical services for mental health concerns ("referred") and to the general population ("non-referred"). A secondary analysis of data from the National Database for Autism Research was used to explore GV using a child behavior checklist, parent report, in 176 children aged 6 to 18 year with ASD compared to referred and non-referred cohorts. GV was present in 4.0% of the ASD group, higher than for the non-referred group (0.7%) but similar to the referred group (4.0%). There were no significant sex differences in GV prevalence (males 3.7%, females 6.0%) in the ASD group. That the GV rate was elevated in ASD relative to non-referred samples but similar to clinically referred samples suggests that elevated rates of GV were not specific to ASD and may be more broadly associated with neurodevelopmental and psychiatric disorders of childhood. Further population-based research using clinical assessment for gender dysphoria is required in individuals with ASD and other neurodevelopmental disorders.